2015
DOI: 10.4049/jimmunol.1500277
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolism Inhibits Antibody-Driven Kidney Injury by Inducing Autophagy

Abstract: Inflammatory kidney disease is a major clinical problem that can result in end-stage renal failure. Here we show that antibody mediated inflammatory kidney injury and renal disease in a mouse nephrotoxic serum nephritis (NTN) model was inhibited by amino acid metabolism and a protective autophagic response. The metabolic signal was driven by IFN-γ-mediated induction of indoleamine 2,3 dioxygenase 1 (Ido1) enzyme activity with subsequent activation of a stress response dependent on the eIF2α kinase general cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 62 publications
5
32
0
Order By: Relevance
“…We previously demonstrated that IL-10 was responsible for IDO1 induction in cells of lepromatous patients [55]. More recently, the IDO1–EIF2AK4/GCN2 axis has been associated with the induction of autophagy in renal cells, enacting a beneficial role in controlling fatal inflammation in mice [56]. The objective of our future studies is to investigate the IDO1–EIF2AK4/GCN2 axis in L-lep leprosy and the immune regulatory components associated with autophagy induction or blockage.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that IL-10 was responsible for IDO1 induction in cells of lepromatous patients [55]. More recently, the IDO1–EIF2AK4/GCN2 axis has been associated with the induction of autophagy in renal cells, enacting a beneficial role in controlling fatal inflammation in mice [56]. The objective of our future studies is to investigate the IDO1–EIF2AK4/GCN2 axis in L-lep leprosy and the immune regulatory components associated with autophagy induction or blockage.…”
Section: Discussionmentioning
confidence: 99%
“…IDO supports interleukin (IL)-6 production through GCN2 activation and was revealed to affect myeloid-derived suppressor cell function and tumor progression (15). A previous study in nephritis mouse models, conducted by Chaudhary et al (16), suggested that kidney injury of mice were improved by amino acid metabolism and protected from the autophagic response. The IFN-γ-mediated induction of IDO activity with subsequent activation of GCN2 is implied in the metabolic signaling process.…”
Section: Ido Depletes Tryptophan and Produces Bioactive Downstream Mementioning
confidence: 99%
“…154 Interestingly, the indoleamine 2,3-dioxygenasegeneral control nonderepressible 2 pathway in podocytes and other cells was suggested to be a critical negative feedback cascade that limits inflammatory renal injuries by inducing autophagy in a model of nephrotoxic serum nephritis. 155 Increasing kidney indoleamine 2,3-dioxygenase 1 activity or treating mice with a general control nonderepressible 2 agonist induced autophagy and protected mice from nephritic kidney damage. Interestingly, kidneys from patients with antibody-driven nephropathy showed increased indoleamine 2,3-dioxygenase 1 abundance and stress gene expression, suggesting interplay between autophagy and interferong-mediated protective feedback cascade.…”
Section: Autophagy In Aging and Diseased Kidneysmentioning
confidence: 99%
“…Interestingly, kidneys from patients with antibody-driven nephropathy showed increased indoleamine 2,3-dioxygenase 1 abundance and stress gene expression, suggesting interplay between autophagy and interferong-mediated protective feedback cascade. 155 Autophagy in DN. DN is the leading cause of end-stage renal disease in industrialized countries.…”
Section: Autophagy In Aging and Diseased Kidneysmentioning
confidence: 99%